Improving Cost-Effectiveness in the Health Care Sector in Iceland - Suppanz, Hannes (OECD Economics Department Working Papers, 2008)
Health outcomes and the quality of health care in Iceland are very good by international comparison, while income-related health inequality appears to be smaller than in most other countries. However, the health-care system is costly and, according to OECD estimates, public expenditure on health and long-term care could reach 15% of GDP by 2050 if no restraining measures are taken. This highlights the importance of raising cost-effectiveness and spending efficiency more generally. To this end, it would seem advisable to remove impediments to private provision and open up the health sector to competition. At the same time, the introduction of cost-sharing should be considered where it does not exist (as in hospitals), although concerns about equity need to be taken into account. This would relieve the burden on public finances, as would the introduction of spending ceilings, cost-efficiency analysis and activity-based funding arrangements. The high cost of pharmaceuticals should be reduced by promoting competition and the use of inexpensive generic drugs